2013
DOI: 10.1155/2013/708785
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on the Food Package Temperature in Refrigerated Display Cabinet Influenced by Indoor Environment

Abstract: In order to study the relation between the food package temperature and ambient environment, the food package temperature is investigated by numerical simulation under the different conditions, such as evaporator outlet velocities, ambient temperatures, and relative humidity. In the present computation, the influence of mass transfer and radiation is considered. The computational results show that the front and top food package temperature rises to 0.1 ∼ 1.2 ∘ C due to the effect of light. At the investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…With the formation of the air jet effect in the air curtain, the packages 7 and 8 given in Figure 3 with the highest package temperatures were kept within the temperature range required by the standard. Zhijuan et al (2013) examined the relationship between cooled package temperature and environment. They noted that when the velocity of the air curtain increased by 0.15 m/s, there was a decrease in the temperature of the packages by 0.2 °C ~ 1.1 °C [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the formation of the air jet effect in the air curtain, the packages 7 and 8 given in Figure 3 with the highest package temperatures were kept within the temperature range required by the standard. Zhijuan et al (2013) examined the relationship between cooled package temperature and environment. They noted that when the velocity of the air curtain increased by 0.15 m/s, there was a decrease in the temperature of the packages by 0.2 °C ~ 1.1 °C [16].…”
Section: Resultsmentioning
confidence: 99%
“…Zhijuan et al (2013) examined the relationship between cooled package temperature and environment. They noted that when the velocity of the air curtain increased by 0.15 m/s, there was a decrease in the temperature of the packages by 0.2 °C ~ 1.1 °C [16]. Wu et al…”
Section: Resultsmentioning
confidence: 99%
“…Despite there were no significant differences between mean thermal sensation votes (TSV) expressed by men and women, from the analysis of the distribution of votes and the percentage of dissatisfied calculated according to Fanger's approach (percentage of persons who voted ±2 and ±3 [11,73]) women appeared more unsatisfied. Particularly, in C1 (D1) PD F value for women was 10% (22%) instead of 0% (13%) in case of men.…”
Section: Local Thermal Discomfortmentioning
confidence: 95%
“…Zhijuan et al [13] investigated the relationship between food package temperature and internal environment. This study revealed that the temperature of the cooling cabinet is affected by light, outdoor airflow, and partial humidity.…”
Section: Introductionmentioning
confidence: 99%